2020
DOI: 10.1021/acsomega.9b03748
|View full text |Cite
|
Sign up to set email alerts
|

From Silver Plates to Spherical Nanoparticles: Snapshots of Microwave-Assisted Polyol Synthesis

Abstract: The fabrication of silver nanoparticles (Ag NPs) with different sizes by microwave (MW)-assisted synthesis is presented. The fast heating of the MW technique, combined with the possibility to thermally quench the reactions, enabled us to capture snapshots of nucleation and growth processes difficult to accomplish in other techniques. The Ag NPs were synthesized using poly(vinylpyrrolidone) (PVP) through a polyol approach. The effects of the reaction time, the reaction temperatures, and the silver precursor con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…It was also concluded that EZE is molecularly dispersed in the lipid matrix, indicating its reduction in crystallinity as the peak intensity of the drug was found to be reduced as shown in Figure 4 . It was also reported earlier that the shift of the peak and reduction in peak height whether in lipid or drug can be attributed to the matrix which was composed of the mixture of lipids [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…It was also concluded that EZE is molecularly dispersed in the lipid matrix, indicating its reduction in crystallinity as the peak intensity of the drug was found to be reduced as shown in Figure 4 . It was also reported earlier that the shift of the peak and reduction in peak height whether in lipid or drug can be attributed to the matrix which was composed of the mixture of lipids [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 87%
“…According to work done by Proetto et al, particles at some locations may begin to coalesce over time, owing to electron-beam induced impairment [ 32 ]. Additionally, Torras et al, stated that the loss of discrete particles might be attributed to higher temperatures [ 33 ]. We assume, this could be due to the slight melding of particle surfaces, for instance during the cooling phase of the nanoemulsion.…”
Section: Resultsmentioning
confidence: 99%
“…These silver nanoparticles were spherical and non-agglomerated [ 21 ]. Recently, it has been demonstrated that the polyol process produces spherical nanoparticles with different sizes under laser ablation [ 17 , 22 ]. To examine the effects of laser wavelength on the particle size, silver nanoparticles were synthesised through ablation with different lasers and it was noticed that decrease in laser wavelength reduced the average diameter of particles from 29 to 12 nm [ 23 ].…”
Section: Synthesis/production Of Silver Nanoparticlesmentioning
confidence: 99%
“…Form another point of view, the development of the NPs from the laboratory to the market is progressing at a low pace. This requires that the method for producing the NPs be well scalable and repeatable [20]. The conventional heating method adopted in many synthesis procedures results in a nonuniform out-of-control nucleation stage that ends up with a relatively wide range of particle sizes and morphologies, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The MW-assisted synthesis can be scaled up to accelerate the commercialization of the NPs. Using the MW-assisted polyol method, Torras and Roig [20] could improve the yield of NP production to 61%, obtaining 1 mg of silver per batch. Following a similar approach, Helmlinger et al [31] obtained 20 mg of Ag per batch, corresponding to a yield beyond 98%.…”
Section: Introductionmentioning
confidence: 99%